Influence of growth regulator akm on biochemical composition of tomato fruit and its change during its storage - Kalytka, Valentyna; Калитка, Валентина Васильевна; Калитка, Валентина Василівна; Karpenko, Kostiantyn; Карпенко, Константин Маркович; Карпенко, Костянтин Маркович (My University, 2014)
En: The main aim of our research was to study the influence of the growth stimulator AKM on the amount of nutrients and physiologically active substances and the shelf life of tomatoes (varieties Eleonora and Klondike) in dry steppe conditions. Water solution of AKM (active substance 3.10-5 g/l) was used for soaking the seeds before planting and for spraying the vegetating tomato plants. The research proves that the application of AKM increased the amount of dry matter (by 0.44%), sugars (0.32%), ascorbic acid and b-carotene (7.5-11.3%) in the fruits, improved their shelf life and increased the fruit storage period by 7-10 days. The decay of nutrients and biologically active substances decreased, which makes it possible to store the products for 30 days and keep their normal quality.
Keywords: lycopersicon esculentum; growth regulator; tomatoes; chemical composition; shelf life